A web 3D service for navigation applications - Haist, Jorg; Thorsten, Reitz; Volker, Coors (2007)
The paper focuses on the actual and upcoming developments of web services that provide 3D spatial data for several client devices. The Fraunhofer Institute for Computer Graphics is actively involved into the development of a Web3D Service and has implemented extensions to this service proposal. Having a look at these extensions we will describe the motivation, the implementation, and the application in different areas, especially navigation systems. By using mobile devices in navigation applications the performance problems of low bandwidths have to be solved. To transfer 3D data, different extending approaches like compression to reduce idle time are presented. Applications for cyclists, hikers and tourists building up on these approaches are described. Here, we concentrate on visualization aspects like height profiles or the 3D visualisation on cell phones.